TECHNIQUES FOR IMPROVING THE EFFECTIVENESS OF WOMEN LABOUR PROTECTION MANAGEMENT - Narziev Shovkiddin Murtozaevich; Jumanazarov Behzod Shonazarovich (Journals Park Publishing, 2022)
This article examines the theoretical and practical aspects of women labour protection management, the impact of working conditions on the labour process through the highly effective use of workers ' working and leisure time. In the unfavorable working conditions created, unhappy employees and occupational diseases arising as a result of various physiological stresses are classified. In the process of Labor, the amount of work was calculated and analyzed according to its physical exertion.
Keywords: Labor Protection; time of work and rest; labor efficiency